(untitled) (Nepal Journal of Neuroscience, 2025)
Introduction: The aim of the study was to compare the frequency of postoperative infection in cerebrospinal fluid shunts performed with and without topical vancomycin at a tertiary care hospital. Materials and Methods: An Observational Cohort Study was conducted from 10th October, 2020 to 9th April, 2021 at Pakistan Institute of Medical Sciences, Islamabad, Pakistan. Total 74 patients of both genders with ages in the range of 1-5 years undergoing cerebrospinal fluid shunts were selected. Patients were divided into two groups (Group A and Group B). Patients with meningitis and ventriculitis before the shunt surgery were excluded. Patients in both the groups received cefotaxime 50 mg/kg body weight intravenously within 60 minutes prior to skin incision and underwent standard cerebrospinal fluid shunt procedure. In the study group (Group B), 10 mg of vancomycin was diluted in 8 ml of normal saline and was divided into two halves. One half was injected in the reservoir of the cerebral shunt and the second half was inﬁltrated subcutaneously around the reservoir and peritoneal catheter. Standard postoperative care was provided to all the patients. Postoperatively, all the patients received intravenous cefotaxime 50 mg/kg body weight repeated 8 hourly for 72 hours. They were monitored for any signs of infection and shunt infection was labelled. Results: Majority of the patients 54 (72.97%) were between 1 to 3 years of age with overall mean age of 2.43 ± 1.28 years. In this study, frequency of postoperative infection was observed to be significantly lower in patients undergoing shunting with versus without topical vancomycin (2.70% vs 29.73%). Conclusion: This study concluded that the frequency of postoperative infection is found to be significantly lower in patients undergoing cerebrospinal fluid shunting with versus without topical vancomycin.